Comparison of Nahdlatul Ulama and Muhammadiyah's Religious Moderation Strategies in the Context of Contemporary Indonesia - Ahmad Qoni Dewantoro; Masdar Hilmi; Ahmad Muthi’Uddin (Values: Jurnal Kajian Islam Multidisiplin, 2026)
This article aims to comparatively examine the concepts and strategies of religious moderation developed by Nahdlatul Ulama (NU) and Muhammadiyah in the context of contemporary Indonesia. NU represents religious moderation through the concept of Islam Nusantara, which emphasizes the harmonization of Islamic teachings with local culture, while Muhammadiyah promotes the concept of Progressive Islam, which is based on the spirit of tajdid through the purification of teachings and social renewal. This research uses a qualitative method with a comparative study approach based on the analysis of literature and official documents from both organizations. The results of the study indicate that despite differences in their approaches to tradition and culture, NU and Muhammadiyah share fundamental similarities in the theological foundation of religious moderation, national attitudes, and commitment to the Unitary State of the Republic of Indonesia (NKRI) and Pancasila as a national consensus. The strategies of religious moderation developed by both organizations play a crucial role in strengthening the values of tolerance, maintaining social stability, and fostering religious harmony amidst the plurality of Indonesian society. Therefore, Islam Nusantara and Progressive Islam can be understood as two distinct yet complementary approaches to moderation in building a peaceful and inclusive religious life.